2000
DOI: 10.1029/1999je001206
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement and composition of steep‐sided domes on Venus

Abstract: Abstract. Steep-sided domes on Venus have surface characteristics that can provide information on their emplacement, including relatively smooth upper surfaces, radial and polygonal fracture patterns, and pits. These characteristics indicate that domes have surface crusts which are relatively unbroken, have mobile interiors after emplacement, and preserve fractures from only late in their history in response to endogenous growth or sagging of the dome surface. We have calculated the time necessary to form a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 83 publications
2
56
0
Order By: Relevance
“…Some cases were found where stereo data show portions of the central depressed areas of domes at similar elevations to the surroundings. Only two of the domes examined by Stofan et al [2000] showed evidence for elevated central vent structures that characterize many terrestrial silicic domes, including the Inyo domes.…”
Section: Comparison To Venusian Domesmentioning
confidence: 99%
See 3 more Smart Citations
“…Some cases were found where stereo data show portions of the central depressed areas of domes at similar elevations to the surroundings. Only two of the domes examined by Stofan et al [2000] showed evidence for elevated central vent structures that characterize many terrestrial silicic domes, including the Inyo domes.…”
Section: Comparison To Venusian Domesmentioning
confidence: 99%
“…Pavri et al [1992] found the majority of the 145 domes examined were in the first two categories: inverted bowl-shaped or flat-topped. However, a survey of 175 domes with diameters >19 km [Stofan et al, 2000], and analyses of stereo pairs for this study, indicate that the ''annular'' type profile (i.e., concave-up) is at least as common as the flat-topped or inverted bowl-shaped types. Some cases were found where stereo data show portions of the central depressed areas of domes at similar elevations to the surroundings.…”
Section: Comparison To Venusian Domesmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical volcanic landforms include lava flow fields, lava channels and steep-sided domes (Crumpler & Aubele 2000; Stofan et al 2000;Magee & Head 2001). Lava flow fields are composed of very long (up to 1000 km) digitated flows, both with radar bright (interpreted to be aa-type lavas) or dark (pahoehoe-type lavas) surfaces, which erupted from shield volcanoes and fissures (including those of coronae).…”
Section: Volcanismmentioning
confidence: 99%